Soft, skin-interfaced electronics enable cannula-free wireless monitoring of sleep respiration - Byeongjun Lee; Hoon Yi; Jungmin Kim; Jimin Lee; Seong J. Cho; Woon-Hong Yeo (Proceedings of the National Academy of Sciences, 2026)
Sleep-related breathing disorders are prevalent yet frequently underdiagnosed, in part due to limitations of conventional respiratory monitoring technologies. Standard nasal cannulas introduce airflow resistance, discomfort, and poor long-term adherence, constraining at-home and longitudinal assessment. Here, we report a soft, skin-interfaced nasal patch that enables cannula-free, wireless monitoring of respiratory activity during sleep. The device is constructed from ultrathin, elastomeric materials that conform to the nasal surface, coupling respiratory-induced tissue deformation to a strain-sensing element. The mechanics of the skin–device interface and the elastomeric response govern the sensitivity and linearity of signal transduction, enabling quantitative capture of breathing dynamics. An integrated wireless platform transmits deformation signals directly to mobile devices, eliminating the need for external tubing or tethered modules. Modular fabrication permits replacement of the strain sensor and skin-contact interface without compromising mechanical performance. Mechanical characterization under physiologically relevant deformation demonstrates high repeatability and low hysteresis, while in vivo studies confirm that the patch accurately reproduces respiratory waveforms and correlates closely with gold-standard nasal cannula measurements. By integrating soft materials mechanics, wearable strain sensing, and wireless electronics, this system provides a minimally obtrusive platform for continuous respiratory monitoring. The class of technologies presented in this work establishes design principles for skin-interfaced devices, in which elastomeric mechanics, strain transduction, and wireless integration combine to enable quantitative, unobtrusive physiological monitoring in clinical and home environments.